Mapping research on health topics presented in prime-time TV dramas in “developed” countries: A literature review - Kato, Mio (Cogent social sciences, 2017)
Some prime-time TV dramas containing health topics have large audiences both in the countries in which they are broadcast as well as on an international level via Internet television network. We conducted a literature review to map the current research articles on prime-time TV dramas with health themes produced in so-called developed countries from 1986 to 2014. The review discovered 59 articles, of which 29 (49.2%) examined the portrayal of patients, doctors, and illness; two (3.4%) examined audience characteristics and motives for watching medical dramas; 17 (28.8%) used cross-sectional methods to examine viewers’ knowledge, attitudes, or behaviors related to health concerns; and 11 (18.6%) used either pre- and post-exposure or post-exposure and follow-up tests to assess changes in viewers’ knowledge, attitudes or behaviors related to health concerns. Theories employed to understand changes in viewers’ knowledge and behaviors included cultivation theory, narrative transportation theory, and social cognitive theory. We noted that even viewers who are disinterested in health issues can be exposed to such content with minimal resistance; dramas and movies can be continuously and affordably distributed as streaming content; and large financial investments are being made in the entertainment industry around the world. As a means of health information exposure, then, narrative forms of entertainment content (e.g. dramas and films) should continue to be investigated, particularly their positive and negative effects on audiences.